A Weak Maximum Principle for Optimal Control Problems with Nonsmooth Mixed Constraints - de Pinho, M. d. R.; Loewen, P.; Silva, Geraldo Nunes [UNESP] (Springer, 2009)
We derive a weak Maximum Principle for nonsmooth optimal control problem involving mixed constraints under some convexity assumptions. Notably we consider problems with possibly nonsmooth mixed constraints. A nonsmooth version of the positive linear independence of the gradients with respect to the control of the mixed constraints plays a key role in validation of our main result.
Keywords: Optimal control; Maximum principle; Nonsmooth analysis